1992
DOI: 10.1086/171512
|View full text |Cite
|
Sign up to set email alerts
|

Fast dynamic reconnection at X-type neutral points

Abstract: We consider the linear and nonlinear evolution of disturbed magnetic X-type neutral points. The problem is formulated within a unified analytic and computational framework which highlights the essence of the mag netic annihilation process, namely, the coupling of a global convection region to a localized diffusion region surrounding the neutral point. An analytic treatment is given for the case of small disturbances of the equilibrium field in the absence of gas pressure. This problem admits well-defined azimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 3 publications
7
93
0
Order By: Relevance
“…In fact, the exponential growth of the current density indicates that the time for magnetic diffusion to become important will depend on ln η. This is in good agreement with Craig & McClymont (1991;1993) and Craig & Watson (1992) who had previously found that the reconnection rate scales as | ln η| 2 . This means that wave dissipation will be very efficient, and predicts that null points will be the natural locations of linear fast wave energy deposition and preferential heating.…”
Section: Single Two-dimensional Null Pointsupporting
confidence: 92%
See 3 more Smart Citations
“…In fact, the exponential growth of the current density indicates that the time for magnetic diffusion to become important will depend on ln η. This is in good agreement with Craig & McClymont (1991;1993) and Craig & Watson (1992) who had previously found that the reconnection rate scales as | ln η| 2 . This means that wave dissipation will be very efficient, and predicts that null points will be the natural locations of linear fast wave energy deposition and preferential heating.…”
Section: Single Two-dimensional Null Pointsupporting
confidence: 92%
“…Again, this result was the first to indicate a relationship between Alfvén wave propagation and the location of the separatrices. An alternative approach to the study of MHD wave behaviour in the neighbourhood of a 2D magnetic null point was investigated in a series of papers by Craig and co-workers (Craig & McClymont 1991;1993;Craig & Watson 1992) in which the authors considered perturbations of the flux function Az. Here, the focus was on applications for magnetic reconnection, specifically to investigate if null points (viewed as weaknesses in the magnetic field) could collapse in response to imposed boundary motions.…”
Section: Why Is This Area Of Study Interesting or Important?mentioning
confidence: 99%
See 2 more Smart Citations
“…Bulanov & Syrovatskii (1980) provided a detailed discussion of the propagation of fast and Alfvén waves using cylindrical symmetry. Craig & Watson (1992) mainly consider the radial propagation of the m = 0 mode (where m is the azimuthal wavenumber) using a mixture of analytical and numerical solutions. They show that the propagation of the m = 0 wave towards the null point generates an exponentially large increase in the current density and that magnetic resistivity dissipates this current in a time related to log η.…”
Section: Introductionmentioning
confidence: 99%